Model Kebijakan Tax Amnesty Berbasis Nilai Keadilan Untuk Meningkatkan Kepatuhan dan Penerimaan Pajak - Winedar, Mustika; Handayani, Alberta; Horri, Miftahol; Nurhayati; Tyas, Alvy Mulyaning; Sayidah, Nur; Assagaf, Aminullah (INVENTORY: JURNAL AKUNTANSI, 2025)
The purpose of this research in the long term is to increase taxpayer compliance in fulfilling tax obligations. The specific goal to be achieved is to create a tax amnesty policy model based on the value of justice that can make taxpayers aware and motivate taxpayers to become compliant taxpayers and not to avoid taxes.  Changes to a fairer tax amnesty policy in the future are the task of government management in order to realize social justice for all Indonesian people. Fair tax policy will be one of the social policies that has an impact on raising public awareness to comply with tax regulations and increase tax revenue. Furthermore, high revenue in the tax sector is one of the important parts in supporting government independence in financing state spending. This study uses a qualitative approach to explore the values of justice in the context of tax. Research data was collected through FGD whose participants consisted of taxpayer representatives, tax officials, tax consultants, and academics. The results of the FGD were analyzed by a coding method which was then used to design a fairness-based tax amnesty model. The resulting research output is the design of a fair tax amnesty model to increase tax compliance and revenue.